Contribution of Islamic Law Concerning The Death Penalty to the Renewal of Indonesian Criminal Law - Muhyidin, Muhyidin; Adhi, Yuli Prasetyo; Triyono, Triyono (Universitas Negeri Semarang, 2022)
This paper aims to describe and analyze the contribution of Islamic law in the regulation (policy formulation) of the death penalty in the context of reforming the national criminal law. Determining the death penalty as a means to tackle crime is a policy choice because capital punishment is a pro and con issue among legal experts. Because the debate about the death penalty is related to the right to life which in international legal instruments and the 1945 Constitution is included in the category of rights that cannot be reduced under any circumstances (non-derogable rights). Islamic law recognizes the death penalty in a crime that has been determined by Allah SWT. in the Al-Qur’an. The death penalty in Islam gives its color with the idea of ​​balance that does not only focus on the perpetrators of the crime but also the victim. Of course, this idea of ​​balance is following the basic values ​​of Pancasila. The death penalty in Islam in the qishahs punishment recognizes the concept of forgiveness from the victim’s family which needs to be developed in the future, especially in the draft Criminal Code which until now has not been ratified as a means for national law reform.